Risk Assessment in Road Transport. Operational Perspective of the Fire Service in Poland - Pawel Gromek; Rafal Wrobel (Communications - Scientific letters of the University of Zilina, 2020)
The paper presents a fire service determined picture of road safety in Poland in its operational (non-system and system) dimensions. It focuses on the road risk assessment, using data related to interventions conducted in 2015-2019 by entities of the State Firefighting Rescue System. The database of the Main Headquarters of the State Fire Service in Poland is adopted and 661,775 emergency road interventions are taken into account.The results state general framework for procedures, resource allocation and training for fire services. The framework is determined by the riskiest kinds of events on the Polish roads. It refers to micro scale (in relation to operational procedures, tactics and strategies, allocation of equipment and training programs) and macro scale (regarding to emergency system, central-planned equipment procurements and training framework).